Before the “Ecologically Noble Savage”: Gendered representations of Amazonia in the global media in the 1970s - Sarzynski, Sarah (Latin American Perspectives, 2021)
An analysis of media representations of the Amazon and indigenous peoples reveals how media producers and filmmakers foregrounded discourses naturalizing gendered and racialized differences that distinguished the Amazon from the West in the 1970s, a decade during which the Brazilian military dictatorship promoted development projects in Amazonia. These representations often sexualized indigenous peoples and the Amazon itself, portraying them as primitive, cannibal savages, animals or part of nature, or victims of exploitation. The “Othering” of the Amazon and Amazonians was further elaborated through a discourse of binary oppositions that portrayed Western white men as explorers and exploiters who dominated the screen, scripts, studies, and development projects even if they were doomed to fail. By relying on a symbolic system of difference, global media coverage and films about Amazonia in the 1970s were complicit in legitimizing authoritarian decrees promoting large-scale development that depicted indigenous peoples and the environment as obstacles. Un análisis de las representaciones mediáticas de la Amazonía y sus pueblos indígenas revela cómo, en la década de 1970, productores y cineastas mediáticos resaltaron discursos que naturalizaron las diferencias de género y racializadas con las que se distinguían a la Amazonía del Occidente en una época durante la cual la dictadura militar brasileña promovió proyectos de desarrollo en la región. Dichas representaciones a menudo sexualizaban a los pueblos indígenas y a la Amazonía misma, retratándolos como primitivos, caníbales salvajes, animales o elementos naturales, o víctimas de explotación. La “otredad” de la Amazonía y los amazónicos se elaboró a través de un discurso de oposiciones binarias que retrataba a los hombres blancos occidentales como exploradores y explotadores que dominaban la pantalla, los guiones, los estudios y los proyectos de desarrollo, incluso si estos estaban condenados al fracaso. Al confiar en un sistema simbólico de diferencia basado en oposiciones binarias y estereotipos, la cobertura mediática global y las películas sobre la Amazonía en la década de 1970 fungieron como cómplices en la legitimación de los tipos de proyectos y políticas llevados a cabo en la región. © 2021 Latin American Perspectives.
Keywords: amazonie; amériques; approches et analyses; brésil; discipline; domination blanche; domination masculine; histoire; histoire et politique; médias; peuples autochtones; projet charge mentale; racisme; régions géographiques; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques; violences; violences coloniales; violences racistes; violences sexistes

Les lieux de la culture: une théorie postcoloniale - Bhabha, Homi K.; Bouillot, Françoise (Éditions Payot & Rivages, 2019)
Sommaire"Salué aussi bien par Edward Said que par Toni Morrison ou J.M. Coetzee, Homi K. Bhabha est l un des théoriciens les plus importants et les plus influents du postcolonialisme. S'appuyant sur la littérature, la philosophie, la psychanalyse et l'histoire, il invite notamment à repenser les questions très actuelles d'identité et d'appartenance nationales ; à dépasser, grâce au concept très fécond d'hybridité culturelle, la vision d'un monde dominé par l'opposition entre soi et l'autre ; à saisir comment, par le biais de l'imitation et de l'ambivalence, les colonisés introduisent chez leurs colonisateurs un sentiment d'angoisse qui les affaiblit considérablement ; ou encore, plus largement, à comprendre les liens qui existent entre colonialisme et globalisation." – Résumé de l'éditeur.
Keywords: approches et analyses; arts; com5170; cours; discipline; har4600; histoire; histoire et politique; identités; philosophie; postcolonialisme; premier cycle; psychanalyse; sciences; sciences humaines; système colonial; systèmes d'oppressions; thématiques; études littéraires

L'importance d'un nom : l'adoption des patronymes à Wendake et à Kahnawake, du milieu du XVIIIe siècle au milieu du XXe siècle - Ouellet, Jean-Sébastien (Université du Québec à Montréal, 2019)
Le présent mémoire s'intéresse aux mutations nominales chez les habitant·es des Premières Nations des communautés de Wendake et Kahnawake. En étudiant les registres des mariages qui y sont célébrés ainsi que d'autres sources de différentes natures, il nous a été possible de circonscrire les périodes de transition et d'identifier certains facteurs potentiels ayant pu causer ces transformations. La recherche s'intéresse ainsi à deux périodes de transition distinctes, respectivement à la fin du XVIIIe siècle pour Wendake et durant la première moitié du XXe siècle pour Kahnawake. Durant ces périodes, la vaste majorité des membres des deux communautés de tradition matrilinéaire abandonnent leurs noms uniques iroquoiens pour adopter des noms européanisés et la patrilinéarité. Ces deux transformations se distinguent de nombreuses façons, mais semblent toutes deux se manifester dans un processus de co-intégration culturelle. Il nous semble que l'importance de ces transformations a été historiquement sous-estimée et trop rarement documentée, particulièrement en regard de l'importance sociale de la transmission matrilinéaire sur le fonctionnement social et la valorisation des rôles sexués dans les communautés Mohawk et Huronne-Wendat, toutes deux réputées traditionnellement matrilinéaires. _____________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : Kahnawake, Wendake, Mohawk, Huron-Wendat, nom unique, patronyme, nom de famille, genre, race, mutation nominale, transformation nominale, transformation patronymique, nom clanique, matrilinéarité, patrilinéarité, clanisme
https://uqam-bib.on.worldcat.org/oclc/1164147823
Keywords: 1700-1799; 1800-1899; 1900-1999; amériques; approches et analyses; biblioFem*; discipline; histoire; histoire et politique; mémoires/thèses; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques

Mobilisations féminines au Cameroun français dans les années 1940-1950: l’ordre du genre et l’ordre colonial fissurés - Ndengue, Rose (Le Mouvement Social, 2016)
Durant la décennie qui suit la Seconde Guerre mondiale, le Cameroun sous tutelle française, comme tous les territoires de l’Empire colonial français, connaît une effervescence sociale et politique. Celle-ci se traduit par des mobilisations de Camerounaises et une montée en puissance de revendications nationalistes, face à l’insuffisance des réformes politiques et sociales mises en place. Cet article examine la manière dont, en s’inscrivant dans un paysage politique majoritairement masculin, des Camerounaises essayent de faire entendre leur voix en s’organisant pour défendre leurs intérêts. L’analyse des ressorts sur lesquels reposent les mobilisations féminines au Cameroun, met en évidence la dualité qui régit la présence des femmes sur la scène publique dans le contexte colonial. Dans une certaine mesure, leur démarche se situe dans un prolongement de l’imaginaire social dominant, mettant en avant des valeurs domestiques pour justifier une intervention des femmes sur la scène politique. Mais les mobilisations féminines visent également la défense d’un agenda propre aux femmes, ainsi que l’émergence d’un nouvel imaginaire social régi par l’égalité des sexes.
Keywords: 1900-1999; 1940-1949; 1950-1959; afrique; afro-féminisme; approches et analyses; cameroun; cours; discipline; discours dominant; féminisme africain; histoire; histoire et politique; militance; pol4022; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; science politique; science politique et droit; sciences humaines; sexisme; système colonial; systèmes d'oppressions; thématiques

Le genre d’une migration post-coloniale : de Meknès (Maroc) à Montréal (Québec) - Yolande Cohen (Genre & Histoire, 2010)
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; afrique; afrique du nord; amériques; approches et analyses; canada; cours; discipline; ethnographie; france; his4830; histoire; histoire du féminisme; histoire et politique; immigration; justice sociale; maghreb; maroc; migration; militance; mouvements des femmes*; mouvements féministes; point de vue situé; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques

La violence nazie, une généalogie européenne - Traverso, Enzo (La Fabrique, 2002)
La violence nazie ne doit rien au hasard: elle a une généalogie, qui n'est pas spécifiquement allemande, et un laboratoire, l'Europe libérale du XIXe siècle.Les camps d'extermination sont l'aboutissement d'un long processus de déshumanisation et d'industrialisation de la mort, amorcé par la guillotine et qui a progressivement intégré la rationalité du monde moderne, celle de l'usine, de la bureaucratie, de la prison. On peut trouver les origines culturelles du nazisme dans le "racisme de classe" qui triomphe après la Commune, dans le discours impérialiste sur l'"extinction des races inférieures" visant à légitimer les génocides coloniaux, enfin dans l'émergence d'une nouvelle image du juif- axée sur la figure de l'intellectuel - comme métaphore d'une maladie du corps social.Le nazisme réalisera la convergence entre ces différentes sources matérielles et idéologiques. Auschwitz se révèle ainsi - et c'est là que réside, selon Enzo Traverso, sa singularité - comme la synthèse d'un ensemble de modes de pensée, de domination et d'extermination profondément inscrits dans l'histoire occidentale.
disponible en ligne : https://shs-cairn-info.proxy.bibliotheques.uqam.ca/la-violence-nazie–9782913372146?lang=fr donné en lecture au cours POL5480, p.44-91.
Keywords: 1900-1999; 1930-1939; 1940-1949; allemagne; approches et analyses; cours; discipline; europe; histoire; histoire et politique; pol5480; premier cycle; périodes historiques; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; violences

Same sex, different cultures: exploring gay and lesbian lives - Herdt, Gilbert H. (Westview Press, 1997)
Because homoerotic relations can be found in so many cultures, Gilbert Herdt argues that we should think of these relations as part of the human condition. This new cross-cultural study of gays, lesbians, and bisexuals around the world, Same Sex, Different Cultures provides a unique perspective on maturing and living within societies, both historical and contemporary, that not only acknowledge but also incorporate same-gender desires and relations. Examining what it means to organize "sex" in a society that lacks a category for "sex", or to love someone of the same gender when society does not have a "homosexual" or "gay/lesbian" role, Herdt provides provocative new insights in our understanding of gay and lesbians lives. Accurate in both its scientific conceptions and wealth of cultural and historical material, examples range from the ancient Greeks and feudal China and Japan to the developing countries of Africa, India, Mexico, Brazil, and Thailand, from a New Guinea society to contemporary U.S. culture, including Native Americans. For all of these peoples, homoerotic relations emerge as part of culture and not separate from history or society. In many of these groups, loving or engaging in sexual relations is found to be the very basis of the local cultural theory of "human nature" and the mythological basis for the cosmos and the creation of society. The mistake of modern Western culture, Gilbert contends, is to continue the legalization of prejudice against lesbians and gays. In this light, the book addresses the issue of "universal" versus particular practices and reveals positive role models that embrace all aspects of human sexuality. Finally, it offers knowledge of the existence of persons who have loved and have been intimate sexually and romantically with the same gender in other lands through divergent cultural practices and social roles. The most important lesson to learn from this cross-cultural and historical study of homosexuality is that there is room for many at the table of humankind.
Keywords: LGBTQIA2+; approche interculturelle; approches et analyses; cours; discipline; discours dominant; histoire; histoire et politique; hétérosexisme; patriarcat; premier cycle; sciences humaines; soc2014; sociologie; système colonial; systèmes d'oppressions; thématiques

America's working women: A documentary history, 1600 to the present - Baxandall, (1939- ...)., Rosalyn Fraad; Gordon, Linda; Reverby, Susan (W.W. Norton, 1995)
A landmark work when it appeared in 1976, America's Working Women helped form the field of women's studies and transform labor history. Now the authors have enlarged the dimensions of this important anthology; more than half the selections and all the introductory material are new. Spanning the years from 1600 to the present, selections from diaries, popular magazines, historical works, oral histories, letters, songs, poetry, and fiction show women's creativity in supporting themselves, their families, and organizations or associations. Slave women recall their field work, family work, and sabotage. We see Indian women farming, and we also see the white culture coercing Indian women to give up farming. We see women in industry playing a central part in the union movement while facing the particular hazards of women's jobs and working conditions. New selections show the historical origins of today's important issues: sexual harassment, equal pay, "sex work," work in the underground economy, work in the home, and shift work. With an expanded focus on women from all racial and ethnic backgrounds and regions, America's Working Women grounds us in the battles women have fought and the ones they are in the process of winning.
Accessible en ligne : https://archive.org/details/isbn_9780393312621
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amériques; approches et analyses; cours; discipline; discours dominant; droits des femmes*; famille; his4443; histoire; histoire des femmes*; histoire et politique; inégalités; premier cycle; périodes historiques; racisme; racisme systémique; rapports sociaux de sexe; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; travail; travail des femmes*; états-unis

In joy and in sorrow: Women, family, and marriage in the Victorian South, 1830-1900 - Bleser, Carol (Oxford Univ. Press, 1991)
In Joy and in Sorrow brings together some of the finest historians of the South in a sweeping exploration of the meaning of the family in this troubled region. In their vast canvas of the Victorian South, the authors explore the private lives of Senators, wealthy planters, and the belles of high society, along with the humblest slaves and sharecroppers, both white and black. Stretching from the height of the antebellum South's pride and power through the chaos of the Civil War and Reconstruction to the end of the century, these essays uncover hidden worlds of the Southern family, worlds of love and duty–and of incest, miscegenation, and insanity. Featuring an introduction by C. Vann Woodward, Pulitzer Prize-winning author of Mary Chesnut's Civil War, and a foreword by Anne Firor Scott, author of The Southern Lady, this work presents an outstanding array of historians: Eugene Genovese, Catherine Clinton, Elizabeth Fox-Genovese, Carol Bleser, Drew Faust, James Roark, Michael Johnson, Brenda Stevenson, Bertram Wyatt-Brown, Jacqueline Jones, Peter Bardaglio, and more. They probe the many facets of Southern domestic life, from the impact of the Civil War on a prominent Southern marriage to the struggles of postwar sharecropper families. One author turns the pages of nineteenth century cookbooks, exploring what they tell us about home life, housekeeping, and entertaining without slaves after the Civil War. Other essays portray the relationship between a Victorian father and his devoted son, as well as the private writings of a long-suffering Southern wife. In Joy and in Sorrow offers a fascinating look into the tangled reality of Southern life before, during, and after the Civil War. With this collection of essays, editor Carol Bleser provides a powerful new way of understanding this most self-consciously distinct region. In Joy and in Sorrow will appeal to everyone interested in marriage and the family, the problems of gender and slavery, as well as in the history of the South, old and new.
Papers of the "Forth Hill Conference on Southern Culture", held at Clemson Univ. (1989). Textes de Fort Hill Conference on Southern Culture, tenue à Clemson University au printemps de 1989.
Keywords: 1800-1899; Noires américaines; amériques; approches et analyses; conditions des femmes*; cours; discipline; famille; his4443; histoire; histoire des femmes*; histoire et politique; inégalités; mariage; patriarcat; premier cycle; périodes historiques; racisme; rapports sociaux de sexe; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; états-unis; états-unis (sud)